Lactobacillus plantarum strain HT-W104-B1: potential bacterium isolated from Malaysian fermented foods for control of the dermatophyte Trichophyton rubrum - Danial, Azlina Mohd; Medina, Angel; Magan, Naresh (Springer, 2021)
The objective was to screen and evaluate the anti-fungal activity of lactic acid bacteria (LABs) isolated from Malaysian fermented foods against two Trichophyton species. A total of 66 LAB strains were screened using dual culture assays. This showed that four LAB strains were very effective in inhibiting growth of T. rubrum but not T. interdigitale. More detailed studies with Lactobacillus plantarum strain HT-W104-B1 showed that the supernatant was mainly responsible for inhibiting the growth of T. rubrum. The minimum inhibitory concentration (MIC), inhibitory concentration, the 50% growth inhibition (IC50) and minimum fungicide concentration (MFC) were 20 mg/mL, 14 mg/mL and 30 mg/mL, respectively. A total of six metabolites were found in the supernatant, with the two major metabolites being L-lactic acid (19.1 mg/g cell dry weight (CDW)) and acetic acid (2.2 mg/g CDW). A comparative study on keratin agar media showed that the natural mixture in the supernatants predominantly contained L-lactic and acetic acid, and this significantly controlled the growth of T. rubrum. The pure two individual compounds were less effective. Potential exists for application of the natural mixture of compounds for the treatment of skin infection by T. rubrum.
Keywords: Organic acids; Metabolites; Lactic acid bacteria; Dermatophyte; Anti-fungals